Optimization Dragline on Parameter and Gas Cutting of Laser Beam Machining in SS400 Steel using Taguchi L16 Methods - Rifky Yusron; Bambang Tjiroso; Kukuh Winarso (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Laser cutting is sustainable non-conventional machining. Unlike wire-EDM, laser cutting have ability to process conductive or non-conductive material without adding any conductive layers before. Laser cutting not depends on any tool supplies. In laser cutting operation, energy consumption being main issue. Less error on dragline and surface roughness in laser cutting process is essentials, to meet them need right setting variable process to produce optimal response. Material using 6mm SS400 steel. Variable observed on this research are laser power output has 4 levels 1820W, 2080W, 2340W and 2600W. Cutting gas pressure has 4 levels 0.5 bar, 1 bar, 1.5 bar, and 2 bar. Gas cutting has 2 kind they are Helium (He) and Dinitrogen (N2). Taguchi L16 (4^2 2^1) applied as research design. this research observing perpendicular on edge of laser cutting. The aim of this research is to provide optimum parameter combination of cutting parameter and gas cutting, so as to produce lowest cutting deviation. For manufacturing industries, this can minimize finishing process and number of product rejection. The highest cutting-edge deviation is 0.1125mm, achieved at combination gas pressure 1.5 bar, 2600W power output and Helium gas cutting on second replication. The lowest cutting-edge deviation is 0.0165, achieved at combination gas pressure 0.1 bar, 2600W power output and dinitrogen gas cutting. Based on Taguchi L16 recommendation optimum combination is gas pressure 1 bar, 2080W power output and using dinitrogen gas cutting. On this combination achieved cutting-edge deviation is 0.0158mm. it was 7% lower than the lowest combination.